Hubungan antara Regulasi Emosi dengan Fear of Missing Out (FoMO) pada Remaja (Usia 13-18 Tahun) Pengguna Media Sosial - Ayu Safitri; Nurmina Nurmina (Asian Journal of Islamic Studies and Da'wah, 2026)
Research on the relationship between emotion regulation and Fear of Missing Out (FoMO) among adolescent social media users in Indonesia remains relatively limited, even though adolescents aged 13–18 years are highly intensive users of digital technology. This study aimed to clarify the direction and strength of the relationship between emotion regulation and FoMO among adolescent social media users. A quantitative approach with a correlational study design was employed, involving 165 adolescents aged 13–18 years selected through purposive sampling. Data were collected online via Google Forms using an emotion regulation scale (covering cognitive reappraisal and expressive suppression) and a FoMO scale (covering anxiety, need to belong, addiction, and need of popularity). The instruments demonstrated good reliability, with Cronbach’s alpha values of 0.798 for emotion regulation and 0.872 for FoMO. Data were analyzed using Pearson Product–Moment correlation and simple linear regression with the aid of SPSS. The results indicated a significant positive relationship between emotion regulation and FoMO (R = 0.549; p = 0.000), with an explained variance of 30.2% (R² = 0.302), meaning that a portion of the variance in FoMO among adolescents can be accounted for by their level of emotion regulation. These findings highlight the importance of strengthening emotion regulation in the context of adolescents’ social media use and open opportunities for further research involving additional psychological variables and longitudinal designs to better understand the long-term dynamics of FoMO in the digital generation.